Influential Article Review - A Review Of The Green Management Evolution Via A kuhnian Perspective - Cisneros, Robbie; Buchanan, Cleo; Dodd, Karis (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines sustainability. We present insights from a highly influential paper. Here are the highlights from this paper: The purpose of this study is to examine the evolutionary development of green management. To do this, first, Kuhn’s “paradigm” concept has been operationalized and the development stages of a movement of thought were determined. The green management is then scrutinized within the framework of each of these stages and the impacts of environmentalism in management research and practice are examined. It is concluded that the crises in normal science, existence of a scientific community, the presence of common beliefs, values and norms, and the increasing anomalousness are strengths of the green management. However, the core position of profit orientation in business strategies weakens the green management. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.